Ethnic Differences and Motivation Based on Maslow's Theory on Iranian Employees. - Seyed Hadi Mousavi; Hossein Dargahi (Tehran University of Medical Sciences, 2013)
The aim of this study was to assess the levels of Maslow's hierarchy of needs theory had been fulfilled and to compare the Maslow's hierarchy of needs among Iranian different ethnic groups at Tehran University of Medical Sciences (TUMS).This research was a descriptive-analytical study which conducted among administrative employees of Tehran University of Medical Sciences; Tehran, Iran. The structured questionnaire consisted of 20 questions and demographic details. Each question had 4 parts to measure Maslow's hierarchy of needs. The questionnaire was distributed randomly among 133 employees to fill-up the demographic details and the other questions. Data was collected and analyzed by SPSS software, and One Way ANOVA, T-test, Spearman and Mann Whitney statistical methods.TUMS ethnic groups of the employees placed most importance on Basic, Self-esteem and Self-actualization. In addition, we found that Persians, Mazandaranians, and Turks ethnic groups, scored the most mean for Maslow's hierarchical needs compared to the other ethnic groups.Basic needs and safety needs is available amongst the different ethnic groups in Iran. As though, self-actualization needs are ultimate human goal, Iranian employees' ethnic groups pay emphasis on these needs. We believe that new structures and work practices such as prevailing cultural values and beliefs of the society or the organizations must be explored if Iranian-based organizations want to remain responsive to the needs of the workplace.